Enteric dysfunction and other factors associated with attained size at 5 years: MAL-ED birth cohort study findings. Issue 1 (25th May 2019) - Richard, Stephanie A; McCormick, Benjamin J J; Murray-Kolb, Laura E; Lee, Gwyneth O; Seidman, Jessica C; Mahfuz, Mustafa; Ahmed, Tahmeed; Guerrant, Richard L; Petri, William A; Rogawski, Elizabeth T; Houpt, Eric; Kang, Gagandeep; et al.
ABSTRACT: Background: Poor growth in early childhood has been associated with increased risk of mortality and morbidity, as well as long-term deficits in cognitive development and economic productivity. Objectives: Data from the MAL-ED cohort study were used to identify factors in the first 2 y of life that are associated with height-for-age, weight-for-age, and body mass index z -scores (HAZ, WAZ, BMIZ) at 5 y of age. Methods: A total of 1017 children were followed from near birth until 5 y of age at sites in Bangladesh, Brazil, India, Nepal, Peru, South Africa, and Tanzania. Data were collected on their growth, environmental enteric dysfunction (EED), micronutrient status, enteric pathogen burden, illness prevalence, dietary intake, and various other socio-economic and environmental factors. Results: EED biomarkers were related to size at 5 y. Mean lactulose:mannitol z -scores during the first 2 y of life were negatively associated with all of the growth measures (HAZ: −0.11 [95% CI: −0.19, −0.03]; WAZ: −0.16 [95% CI: −0.26, −0.06]; BMIZ: −0.11 [95% CI: −0.23, 0.0]). Myeloperoxidase was negatively associated with weight (WAZ: −0.52 [95% CI: −0.78, −0.26] and BMIZ: −0.56 [95% CI: −0.86, −0.26]); whereas α-1-antitrypsin had a negative association with HAZ (−0.28 [95% CI: −0.52, −0.04]). Transferrin receptor was positively related to HAZ (0.18 [95% CI: 0.06, 0.30]) and WAZ (0.21 [95% CI: 0.07, 0.35]). Hemoglobin was positively related to HAZ (0.06 [95% CI: 0.00, 0.12]), and ferritin was negatively related to HAZ (−0.08 [95% CI: −0.12, −0.04]). Bacterial density in stool was negatively associated with HAZ (−0.04 [95% CI: −0.08, 0.00]), but illness symptoms did not have any effect on size at 5 y. Conclusions: EED markers, bacterial density, and iron markers are associated with growth at 5 y of age. Interventions to reduce bacterial burden and EED may improve long-term growth in low-income settings.